Carbon Emissions Disclosure: Return on Assets, Leverage and Media Exposure - Lestari, Lestari; Meiwanto Doktoralina, Caturida; Mareta, Sigit; Apriani, Ari; Alhazami, Lutfi (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The purpose of this study is to prove the hypothesis that return on assets, leverage projected by debt to equity ratio and media exposure affect the disclosure of carbon emissions. This type of research uses a quantitative approach. The population in this study are mining companies listed on the IDX in 2018-2022. The total population is 52 companies. Researchers apply a non-probability sampling method, which will specifically be carried out using purposive sampling method, then a total sample of 26 companies is found. The data collection technique used in this exploration is the documentation strategy. Then the data analysis uses multiple linear regression analysis method to analyze the effect of independent variables on the dependent which is processed using Statistical Program for Social Science (SPSS) 25 software program. Based on hypothesis testing, the results show that media exposure has a positive and significant effect on carbon emission disclosure. Meanwhile, Return on Asset and Debt to Equity Ratio have no significant effect on carbon emission disclosure.